Primary Prevention of Cardiovascular and Heart Failure Events With SGLT2 Inhibitors, GLP-1 Receptor Agonists, and Their Combination in Type 2 Diabetes - Wright, Alison K.; Carr, Matthew J.; Kontopantelis, Evangelos; Leelarathna, Lalantha; Thabit, Hood; Emsley, Richard; Buchan, Iain; Mamas, Mamas A.; van Staa, Tjeerd P.; Sattar, Naveed; Ashcroft, Darren M.; Rutter, Martin K. (Diabetes care, 2022)
To assess associations between current use of sodium-glucose cotransporter 2 inhibitors (SGLT2is), glucagon-like peptide 1 receptor agonists (GLP-1RAs), and their combination and risk for major adverse cardiac and cerebrovascular events (MACCE) and heart failure (HF) in people with type 2 diabetes. In three nested case-control studies involving patients with type 2 diabetes in England and Wales (primary care data from the Clinical Practice Research Datalink and Secure Anonymised Information Linkage Databank with linkage to hospital and mortality records), we matched each patient experiencing an event with up to 20 control subjects. Adjusted odds ratios (ORs) for MACCE and HF among patients receiving SGLT2i or GLP-1RA regimens versus other combinations were estimated using conditional logistic regression and pooled using random-effects meta-analysis. Among 336,334 people with type 2 diabetes and without cardiovascular disease, 18,531 (5.5%) experienced a MACCE. In a cohort of 411,206 with type 2 diabetes and without HF, 17,451 (4.2%) experienced an HF event. Compared with other combination regimens, the adjusted pooled OR and 95% CI for MACCE associated with SGLT2i regimens was 0.82 (0.73, 0.92), with GLP-1RA regimens 0.93 (0.81, 1.06), and with the SGLT2i/GLP-1RA combination 0.70 (0.50, 0.98). Corresponding data for HF were SGLT2i 0.49 (0.42, 0.58), GLP-1RA 0.82 (0.71, 0.95), and SGLT2i/GLP-1RA combination 0.43 (0.28, 0.64). SGLT2i and SGLT2i/GLP-1RA combination regimens may be beneficial in primary prevention of MACCE and HF and GLP-1RA for HF. These data call for primary prevention trials using these agents and their combination.